Evaluation of periodontal health of the students in Marmara University Faculty of Dentistry - Kınacı, Anıl; Doğan, Başak (Marmara Üniversitesi Sağlık Bilimleri Enstitüsü Dergisi, 2012)
Objective: Since the dental students are expected to be good example with oral health behaviours and attitudes, to determine their oral health status and attitudes are important. The aims of our study are to assess the periodontal and dental status, oral health behaviours and attitudes of dental students in Marmara University and to identify the differences according to gender, level of education and habits. Method: A total of 538 students participated to our study. After filling out the questionnaire forms, anamnesis were taken, then clinical examination and periodontal measurements were carried out. Results: Brushing teeth 2/more times a day was found in 83.3% of the students and was higher in female, non-smoker and clinical students (p?0.001). Smoking percentage was 23% among all students and was higher in clinical and male students (p<0.01). The mean plaque index (P.I.) of the students was 1.09±0.22, gingival index (G.I.) 0.91±0.19, bleeding on probing (B.O.P.)%14.09±10.18, probing depth (P.D.) 2.17±0.24 mm, clinical attachment loss (C.A.L.) 0.12±0.17 mm, the number of missing teeth 0.52±1.05 and the decayed teeth 2.89±2.79. The mean G.I. and P.D. were higher but B.O.P. and C.A.L. levels were lower in the preclinical students than the clinical students (p?0.05). The mean P.I., B.O.P. and C.A.L. levels were higher in smokers than non-smokers (p<0.01). The low-physical activity percentage was 67% and these students had higher mean B.O.P. and P.D than moderate/high physically-active ones (p?0.05). Conclusion: Students should have a comprehensive programme on oral hygiene and negative effects of smoking starting from first year of education.
Keywords: Dental student, epidemiology, oral hygiene, periodontal disease, periodontal indexes